2019
DOI: 10.1515/opli-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Argument Structure of Classifier Predicates: Canonical and Non-canonical Mappings in Four Sign Languages

Abstract: We analyze argument structure of whole-entity and handling classifier predicates in four sign languages (Russian Sign Language, Sign Language of the Netherlands, German Sign Language, and Kata Kolok) using parallel datasets (retellings of the Canary Row cartoons). We find that all four languages display a systematic, or canonical, mapping between classifier type and argument structure, as previously established for several sign languages: whole-entity classifier predicates are mostly used intransitively, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Tokens of multiple signs associated with the same meaning were therefore collapsed into a single group.⁷ Furthermore, we exclude so-called classifier predicates from our study to only focus on lexical signs. This choice is motivated by the variation found in the argument structure of these signs, although certain types of classifiers have been shown to be associated with particular argument structure alternations crosslinguistically (Benedicto and Brentari, 2004;De Lint, 2018;Kimmelman et al, 2019).⁸ Because of the different natures of the sign language corpora (Section 2.2), we do not find the same amount of tokens for all 25 ValPaL verb meanings in all languages. Kimmelman (2016) set the token threshold to 25 for RSL, but we find that following this same limit decreases the number of comparable verb meanings considerably across our sampled sign languages.…”
Section: Sampling Annotating and Processing Sign Language Data 23mentioning
confidence: 98%
“…Tokens of multiple signs associated with the same meaning were therefore collapsed into a single group.⁷ Furthermore, we exclude so-called classifier predicates from our study to only focus on lexical signs. This choice is motivated by the variation found in the argument structure of these signs, although certain types of classifiers have been shown to be associated with particular argument structure alternations crosslinguistically (Benedicto and Brentari, 2004;De Lint, 2018;Kimmelman et al, 2019).⁸ Because of the different natures of the sign language corpora (Section 2.2), we do not find the same amount of tokens for all 25 ValPaL verb meanings in all languages. Kimmelman (2016) set the token threshold to 25 for RSL, but we find that following this same limit decreases the number of comparable verb meanings considerably across our sampled sign languages.…”
Section: Sampling Annotating and Processing Sign Language Data 23mentioning
confidence: 98%
“…However, Kimmelman et al (2019) found in their NGT data that entity classifiers occasionally combine with an unergative verb, i.e., a verb which expresses an activity performed by an agent.…”
Section: Description Of Represented Entitiesmentioning
confidence: 99%
“…Second, there is a relationship between classifier type and argument structure: Entity classifiers only combine with intransitive classifier predicates, i.e., verbs that only require one argument (e.g. BE_LOCATED and MOVE, as in 'a book lies on the table' or 'a car moves') (Kimmelman et al 2019;de Lint 2018). Most commonly, these are unaccusative verbs, i.e., verbs in which the subject is not an agent, but rather undergoes the action described by the verb (e.g.…”
Section: Description Of Represented Entitiesmentioning
confidence: 99%
See 2 more Smart Citations